Answer:
Step-by-step explanation:
Given the expressions y = 2x and y = -4x, we need to know the greatest one.
From both equations, we can see that the variable y is directly proportional to x as shown:
y α x
y = kx
k is the constant of proportionality
First, we need to get the constant of proportionality for both equations. The greater the constant of proportionality, the greater the equation.
For the equation y = 2x
kx = 2x
k = 2
For the equation y = -4x
kx = -4x
k = -4
Since 2 is greater than -4, this shows that the equation y = 2x is greater.